NILAI-NILAI MORAL DAN AGAMA PADA ANAK USIA DINI - sandra hapsari putri (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2022)
one of the basic attitudes that must be possessed by a child is to have good religious attitudes and morals in behaving as religious people of god. the age of early childhood is a good age to lay the foundations of moral and religious education. Instilling moral and religious values in early childhood is verry important so that children can have good moral and religious values, so that when children enter the next level, children already have knowledge, good experiences that have been obtained when they were still in school. early childhood or kindergarten.